Génesis teórica del Estado - Martínez Barrera, Jorge (ARFIL y UNL, 2018)
The paper traces the origin of the term State, the evolution of its concept and its relation with Right in ancient and medieval philosophy, and focuses then on Machiavelli and the classics of Political Philosophy of modernity. Next it turns to study the emergence of the concept of sovereignty in Bodin and Hobbes, which, together with the corpuses of law, characterize modern State. The exposition ends with the introduction, starting from Locke, of the idea that the first source from which sovereignty originates is the people. And this being so, it becomes clear that the head of the State is a representative of the people or mandatary. The sovereignty of those who preside the State is sovereignty by trust. The way is thus definitely open for the theory of popular sovereignty, which by no means implies a discussion about sovereignty of State. Both are perfectly complementary and one cannot express itself without the other.